2016
DOI: 10.1055/s-0041-111535
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic Retrograde Degeneration: Clinical Evidence with Homonymous RGCL Loss on OCT

Abstract: The homonymous defect of RGCL in patients with retrogeniculate lesions demonstrates the presence of transsynaptic retrograde degeneration. RGCL is a better predictor of visual field defects than RNFL measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…We present a case of a visual field defect of postchiasmal origin, corresponding to neurosurgical intervention for a ruptured aneurysm secondary to an arteriovenous malformation. The OCT findings in our case are consistent with the literature in showing transsynaptic retinal degeneration from a posterior visual pathway insult (1–7). The patient also had a left homonymous hemianopia with corresponding thinning of the macular GCL and ppRNFL (2,3).…”
supporting
confidence: 92%
“…We present a case of a visual field defect of postchiasmal origin, corresponding to neurosurgical intervention for a ruptured aneurysm secondary to an arteriovenous malformation. The OCT findings in our case are consistent with the literature in showing transsynaptic retinal degeneration from a posterior visual pathway insult (1–7). The patient also had a left homonymous hemianopia with corresponding thinning of the macular GCL and ppRNFL (2,3).…”
supporting
confidence: 92%
“…5 Previous studies in the literature demonstrated that abnormalities of macula GCC occurred earlier than peripapillary RNFL thickness. 15,[22][23][24] Moreover, the interpretation of GCC thinning and related visual field loss is easier. It has a simple mirror-image relationship with the visual field, in contrast to the complex relationship between RNFL bundles and visual field sectors that have been mapped previously.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained that in the earlier stage of compression, the conduction block corresponding to ganglion cell axons leads to an enlarged appearance on the peripapillary RNFL, and as the compression persists, the axonal damage may result in progressive RNFL thinning. 19,20 In the current study, the coexistence of RNFL thinning and thickening in different peripapillary quadrants might be related to different stages of the same neurodegeneration process in retinal nerve fibers. 18 The elevated intracranial pressure (ICP) is linked to compressive or ischemic effects on optic nerve.…”
Section: Discussionmentioning
confidence: 59%
“…Besides, a few studies reported significant GC-IPL thinning in brain lesions affecting pre-geniculate or post-geniculate optic pathways which were associated with transsynaptic retrograde degeneration of nerve fibers. 7,16,19 (Figure 5(a)-(d)). In the current study, the sectoral based GC-IPL analysis of inner and outer ring revealed contradictory results between eyes with intracranial tumors associated with pre-geniculate and post-geniculate optic pathway.…”
Section: Reported Thatmentioning
confidence: 99%